ABRUPTIO PLACENTAE: TO MINIMIZE THE RISK - I. N. Medvedevа; K. S. Svyatchenko (IRBIS LLC, 2016)
The analysis of the state of health of pregnant women was made and several risk factors for abruptio placentae were identified. The research was based on a retrospective analysis of 65 birth stories for 2014-2015 on the basis of Regional Perinatal Center of Kursk. We studied the medical history, concomitant somatic pathology and the results of monitoring of pregnancy and childbirth. In the group of studied women 45 (69.23%) of them had a complicated obstetrical and gynecological anamnesis, every second pregnancy was against the background of the threat of interruption, all patients had from 1 to 4 complications of pregnancy; high percentage extragenital primarily to changes in the vascular system of the maternal organism. An increase of various types of pathology complicates the course of pregnancy, including increasing abruptio placentae. This requires pregravid preparation, timely diagnostics and correction of violations, as well as ensuring a close relationship and succession between doctors.